The rural setting thesaurus : a writer's guide to personal and natural places - Ackerman, Angela, ....-; Puglisi, Becca, ....- ([California] : Writers helping writers, 2020)
What if there was a shortcut for helping readers get to know your characters? Would you take it? Characters are as complex as people and revealing their inner layers without chunky blocks of pace-stopping description is a challenge. The Occupation Thesaurus can help you unlock one of the best tools in your show-dont-tell writing kit: a characters job. Occupations are part of our everyday world, meaning they can be used to encourage readers to make associations between a type of work and the person doing it, shortening the 'get to know the character' curve. Whether a person loves or hates what they do, a job can reveal many things, including their priorities, beliefs, desires, and needs. The Occupation Thesaurus will show you how a career choice can characterize, drive the plot, infuse scenes with conflict, and get readers on the characters side through the relatable pressures, responsibilities, and stakes inherent with work.
Keywords: English literature